Maintainability Prediction for Object-Oriented Software Systems Based on Intelligent Techniques: Literature Review - anfal fadhil; Taghreed Alreffaee (Al-Rafidain Journal of Computer Sciences and Mathematics)
The maintainability of the software is one of the most substantial aspects when assessing software product quality. It is known as the easiness with which the current software can be changed. In the literature, a great number of models have been suggested to predict and measure maintainability during various stages of the Software Development Life Cycle, to conduct a comparative study of the existing suggested models of the prediction, only few attempts have been done. This study hints at the basics about the manner of how to measure maintainability in the object-oriented (OO) design knowing that the maintainability will be measured differently at every level. Also, we will concentrate on the artificial intelligence technologies of these studies.